Potential Effect of Exosomes Derived from Cancer Stem Cells and MSCs on Progression of DEN-Induced HCC in Rats - Faisal A. Alzahrani; Mohammed A. El-Magd; Ahmed Abdelfattah-Hassan; Ayman A. Saleh; Islam M. Saadeldin; Eman S. El-Shetry; Abdelnaser A. Badawy; Saleh Alkarim (Stem Cells International)
Cross talk, mediated by exosomes, between normal stem cells and cancer stem cells (CSCs) in the tumor microenvironment has been given less attention so far. In addition, no publications are available in the literature that address the in vivo impact of exosomes derived from CSCs and mesenchymal stem cells (MSCs) on progression of long-term hepatocellular carcinoma (HCC). Herein, we hypothesized that transfer of exosomes among the cells in the HCC microenvironment could either induce or inhibit tumor growth and metastasis depending on their source. To check this hypothesis, we investigated the effect of exosomes coming from two different stem cell populations, hepatic CSCs and bone marrow (BM) MSCs, on progression of long-term DEN-induced HCC in rats and the involved underlying mechanisms. CSCs-exosomes induced a significant increase in liver relative weight and serum levels of cancer markers (AFP and GGT) and liver enzymes (ALT, AST, and ALP), intensive immunostaining for the HCC marker GST-P, and an increased number and area of tumor nodules as compared to HCC rats injected by PBS. CSCs-exosomes also decreased apoptosis (marked by downregulation of Bax and p53 and upregulation of Bcl2, and increased immunostaining of PCNA), increased angiogenetic activity (revealed by upregulation of VEGF), enhanced metastasis and invasiveness (indicated by upregulation of P13K and ERK proteins and their downstream target MMP9 and downregulation of TIMP1), and induced epithelial mesenchymal transition (marked by increased serum and hepatic level of TGFβ1 mRNA and protein). Notably, CSCs-exosomes also elevated HCC exosomal microRNA (miR) 21, exosomal long noncoding (lnc) RNA Tuc339, lncHEIH, and the HCC lncHOTAIR and decreased liver miR122 and HCC miRs (miR148a, miR16, and miR125b). All these cellular, functional, and molecular changes were reversed following injection of BM-MSCs-exosomes. However, both CSCs- and MSCs-exosomes failed to change the elevated oxidative stress or the inhibited antioxidant activities induced by HCC. Collectively, our results revealed a tumor stimulatory effect (induction of tumor growth, progression, and metastasis) for exosomes derived from CSCs and an inhibitory effect for exosomes derived from MSCs. These results provide valuable insight on the effect of CSCs- and MSCs-exosomes on HCC growth and progression in vivo, which may be helpful to understand the mechanism of HCC development.